Custody in Islamic Law: A Law Based on Presumptions - Sabreen, Mudasra (Islamic Studies, 2017)
Custody is a right of the child from its birth. Islamic law issues rules for custody in the light of the interest of the minor. In Islamic law custody goes to the mother unless she is disqualified and then to other relatives. This paper discusses and analyses the rules of child custody in Islamic law and argues that most of these rules are not divine. These are a product of ijtihad. A large extent of these rules is actually presumptions which may be rebutted in a given situation.